Da reocupação ao alagamento:historiografia, memórias e ensino de História no Município de Santa Helena (PR) - Forlin, Talia Mayara Lopes (2023)
This research investigates the construction of discourses that legitimize an official history for the municipality of Santa Helena-PR, as well as its dissemination through municipal public education. From the 1990s, with the recent construction of the Itaipu Hydroelectric Power Plant, the municipal administration sought ways to give a new “path” to the history of the municipality, given the problems generated by the flooding of a large part of the territory. Thus, the municipality began a project aimed at building and idealizing an official history that would direct the history of Santa Helena towards progress. In order to achieve its objectives, the municipal government organized, in the early 2000s, a didactic material that was made available to public schools and should be used with students in the 4th year of elementary school. The notions of history contained in this material were formulated in the same parameters as the project already started, which ensured that the official history already constituted was passed on to several generations of students through municipal public education. In this way, our research proposes to think which perspectives are part of this history, which memories are highlighted, which are silenced and how they are worked in the classroom by network teachers, investigating the intentions and objectives of the public sector, as well as the ways in which local history is taught in schools. To do so, we will analyze the historiography referring to the reoccupation of Santa Helena, interviews with residents who participated in this process, the Curricular Pedagogical Proposal used in the western region of Paraná, the didactic material made available by the city hall to schools and interviews we conducted with 4th grade teachers. As a methodological reference, we will use authors such as Alessandro Portelli, Verena Alberti and Circe Bittencourt.